Heat Stress Mitigation in Resource-Constrained Dairy Farming Systems: Practical Strategies for Sustainable Development - Md. Emran Hossain (International Journal of Climate Conditions, 2025)
Heat stress poses a critical threat to dairy production, particularly in resource-constrained systems prevalent across tropical and subtropical regions. Elevated ambient temperatures, compounded by high humidity, directly impair feed intake, milk yield, reproductive efficiency, and overall animal welfare. In low-resource settings, conventional cooling technologies such as automated fans, sprinklers, and climate-controlled housing remain economically inaccessible. Therefore, cost-effective, locally adaptable, and sustainable solutions are essential for maintaining productivity and animal health. This review consolidates practical heat stress mitigation strategies applicable in economically challenged dairy systems, organized under ten core categories: housing design, shading techniques, water management, feeding practices, ventilation enhancement, bedding and flooring, grazing and animal movement, animal handling, behavioral support, and community-based interventions. The paper emphasizes the integration of passive cooling methods such as shade trees, natural ventilation, and strategic grazing management with behaviourally aligned handling and resource-sharing models. Each category is examined in terms of feasibility, affordability, and impact on animal performance and welfare. Special focus is given to region-specific practices and indigenous knowledge systems that enhance adaptability under climatic extremes. By adopting these tailored interventions, resource-poor dairy producers can significantly alleviate thermal stress, promote animal comfort, and foster sustainable livestock development with minimal financial input. The findings contribute to climate-resilient dairying under economic constraints.
Keywords: Dairy Farming; Heat Stress; low-cost interventions; resource-limited systems; sustainable development